2022
DOI: 10.1177/17448069221089596
|View full text |Cite
|
Sign up to set email alerts
|

Human safety study of a selective neuronal adenylate cyclase 1 inhibitor NB001 which relieves the neuropathic pain and blocks ACC in adult mice

Abstract: Calcium-dependent, neuronal adenylyl cyclase subtype 1 (AC1) is critical for cortical potentiation and chronic pain. NB001 is a first-in-class drug acting as a selective inhibitor against AC1. The present study delineated the pharmacokinetic (PK) properties of human-used NB001 (hNB001) formulated as immediate-release tablet. This first-in-human study was designed as randomized, double-blind, placebo-controlled trial. hNB001 showed placebo-like safety and good tolerability in healthy volunteers. A linear dose-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…We infer that this is mainly due to three major reasons: (i) AC1 is selectively expressed in neurons, and it is not found in other non-neuronal tissues such as heart, kidney, and liver; (ii) AC1 is activated in an activity-dependent manner, and it plays major roles in physiological conditions; (iii) Key brain physiological functions, such as learning and memory, can be compensated by other isoforms of ACs such as AC8 as well as other protein kinases that also contribute to learning-related plasticity (16-18). Consistently with these hypothesis, recent studies in both animals and healthy humans found that NB001 or hNB001 produced no signi cant side effects (7,24,27). In the present study, we found that neither single nor continuous administration of hNB001 affected nociception, motor functions, and anxiety-like behavior in adult and aged mice.…”
Section: Nb001 and The Safety Of Both Humans And Animalssupporting
confidence: 90%
“…We infer that this is mainly due to three major reasons: (i) AC1 is selectively expressed in neurons, and it is not found in other non-neuronal tissues such as heart, kidney, and liver; (ii) AC1 is activated in an activity-dependent manner, and it plays major roles in physiological conditions; (iii) Key brain physiological functions, such as learning and memory, can be compensated by other isoforms of ACs such as AC8 as well as other protein kinases that also contribute to learning-related plasticity (16-18). Consistently with these hypothesis, recent studies in both animals and healthy humans found that NB001 or hNB001 produced no signi cant side effects (7,24,27). In the present study, we found that neither single nor continuous administration of hNB001 affected nociception, motor functions, and anxiety-like behavior in adult and aged mice.…”
Section: Nb001 and The Safety Of Both Humans And Animalssupporting
confidence: 90%
“… 59 , 60 Differing from CGRP antagonists, our previous animal data as well as phase I clinical studies found that NB001 is very safe in both animals and humans. 19 , 30 , 61 The superiority of NB001 in the treatment of migraine lies in that it did not interfere with normal synaptic transmission, but only inhibit the enhanced synaptic transmission under the condition of chronic pain. Hansen et al.…”
Section: Discussionmentioning
confidence: 99%
“… 19 In human studies, no serious adverse event was reported in healthy candidates after the oral administration of NB001. 61 We believe that AC1 can serve as a new drug target for the treatment of chronic migraine, and NB001 is a strong drug candidate and could meet the need for better drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Another adenylate cyclase 1 inhibitor, NB-001, has analgesic effect on cancer pain [ 347 ]. The safety of NB001 is being tested in human clinical trials [ 348 ]. While the chromone-based ST034307 selectively inhibits adenylate cyclase 1 [ 349 ], the oxadiazole-based AC10065 can suppress both adenylate cyclase 1 and adenylate cyclase 8 [ 350 ].…”
Section: Targeting Camp Signaling For Cancer Therapymentioning
confidence: 99%